Merangkul Kembali Yang Terasing: Strategi Praktis Gereja Dalam Memanggil Kembali Jemaat Yang Jarang Beribadah - Simanjuntak, Joksan; Ifraldo Tambun, Roy Haries (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
The increasing number of congregants who rarely attend worship has become a serious challenge for many churches in maintaining spiritual engagement and community commitment. This study aims to identify the factors that cause congregants to distance themselves from worship activities and to explore strategies that churches can implement to reengage alienated members. Using a qualitative approach, this research involved in-depth interviews with 8 selected congregants who had demonstrated inactivity in worship, focusing on a case study at Church HKBP Pardamean. The interview findings revealed several key factors contributing to the lack of attendance, including the rising demands of modern life, individualism influenced by technology, and disappointment with internal church aspects. Based on these findings, the study recommends practical strategies for churches, such as personalized approaches and strengthening the sense of belonging among congregants. This article aims to provide guidance for churches in addressing the issue of congregational disengagement and developing a more inclusive pastoral approach.